Effect of lycopene on cell viability and cell cycle progression in human cancer cell lines - Teodoro Anderson; Oliveira Felipe; Martins Nathalia; Maia Guilherme de; Martucci Renata; Borojevic Radovan (Cancer Cell International, 2012)
Abstract Background Lycopene, a major carotenoid component of tomato, has a potential anticancer activity in many types of cancer. Epidemiological and clinical trials rarely provide evidence for mechanisms of the compound’s action, and studies on its effect on cancer of different cell origins are now being done. The aim of the present study was to determine the effect of lycopene on cell cycle and cell viability in eight human cancer cell lines. Methods Human cell lines were treated with lycopene (1–5 μM) for 48 and 96 h. Cell viability was monitored using the method of MTT. The cell cycle was analyzed by flow cytometry, and apoptotic cells were identified by terminal deoxynucleotidyl transferase-mediated dUTP nick labeling (TUNEL) and by DAPI. Results Our data showed a significant decrease in the number of viable cells in three cancer cells lines (HT-29, T84 and MCF-7) after 48 h treatment with lycopene, and changes in the fraction of cells retained in different cell cycle phases. Lycopene promoted also cell cycle arrest followed by decreased cell viability in majority of cell lines after 96 h, as compared to controls. Furthermore, an increase in apoptosis was observed in four cell lines (T-84, HT-29, MCF-7 and DU145) when cells were treated with lycopene. Conclusions Our findings show the capacity of lycopene to inhibit cell proliferation, arrest cell cycle in different phases and increase apoptosis, mainly in breast, colon and prostate lines after 96 h. These observations suggest that lycopene may alter cell cycle regulatory proteins depending on the type of cancer and the dose of lycopene administration. Taken together, these data indicated that the antiproliferative effect of lycopene was cellular type, time and dose-dependent.